2002
DOI: 10.1038/sj.bjp.0704876
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and potential therapeutic applications of nitric oxide‐releasing non‐steroidal anti‐inflammatory and related nitric oxide‐donating drugs

Abstract: This review examines the biological signi®cance, therapeutic potential and mechanism(s) of action of a range of nitric oxide-releasing non-steroidal anti-in¯ammatory drugs (NO-NSAID) and related nitric oxide-releasing donating drugs (NODD). The slow release of nitric oxide (NO) from these compounds leads to subtle changes in the pro®le of pharmacological activity of the parent, nonsteroidal anti-in¯ammatory drugs (NSAID). For example, compared with NSAID, NO-NSAID cause markedly diminished gastrointestinal tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
155
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(162 citation statements)
references
References 129 publications
(172 reference statements)
3
155
0
4
Order By: Relevance
“…Along this line of research, particular interest has been focused on the generation of NOdonating nonsteroidal anti-inflammatory drugs (NSAID) that consist of NSAID to which an NO-donating group is covalently attached via an aromatic or aliphatic spacer (6). Although these drugs share some of pharmacologic properties with parental compounds, current data indicate that their structural modification is responsible for enhanced potency and diminished toxicity (7). Preclinical studies have shown that NO-NSAIDs are effective in Alzheimer's disease, cardiovascular, rheumatologic, and lung diseases (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line of research, particular interest has been focused on the generation of NOdonating nonsteroidal anti-inflammatory drugs (NSAID) that consist of NSAID to which an NO-donating group is covalently attached via an aromatic or aliphatic spacer (6). Although these drugs share some of pharmacologic properties with parental compounds, current data indicate that their structural modification is responsible for enhanced potency and diminished toxicity (7). Preclinical studies have shown that NO-NSAIDs are effective in Alzheimer's disease, cardiovascular, rheumatologic, and lung diseases (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although these drugs share some of pharmacologic properties with parental compounds, current data indicate that their structural modification is responsible for enhanced potency and diminished toxicity (7). Preclinical studies have shown that NO-NSAIDs are effective in Alzheimer's disease, cardiovascular, rheumatologic, and lung diseases (7). Combination of cyclooxygenase inhibition property of NSAIDs with tumoricidal potential of NO makes these drugs suitable candidates for treatment of malignant diseases (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades a lot of hybrid nitrates as in vivo NO-donors have been studied for their potential use in the treatment of a variety of diseases, including pain and inflammation, thrombosis and restenosis, neurodegenerative diseases, cancer, liver disease, impotence, bronchial asthma and osteoporosis (Keeble and Moore, 2002). Since some disagreement about whether nitrates really generate NO at all, some authors prefer to use the term NO-mimetics (Thatcher et al, 2005).…”
mentioning
confidence: 99%
“…1), NO-aspirin showed pharmacological effects in cardiovascular, cancer and inflammation models, and when tested in clinical trials showed little or no gastric toxicity (Cena et al, 2003;Keeble and Moore, 2002), due to gastro-protective effects of NO . A new class of cyclooxygenase-inhibiting nitric oxide donors (CINODs) has been developed with the aim of achieving greater safety than the existing non-steroidal anti-inflammatory drug (NSAIDs) (Boschi et al, 2010(Boschi et al, , 2009.…”
mentioning
confidence: 99%
See 1 more Smart Citation